2019
DOI: 10.3390/ijerph16020270
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of High-Temperature Weather on Human Sleep Quality and Appetite

Abstract: High-temperature weather appears in high frequency, big strength, and long duration in the summer. It is therefore important to study the effects of high-temperature weather on sleep quality and appetite. Ten healthy college students were selected as subjects. The experiment conditions were divided by the daily maximum temperature into 28 °C, 32 °C, 36 °C, and 38 °C. The objective sleep quality was measured by an intelligent sleep monitoring belt, and the subjective sleep quality was measured by a questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 26 publications
2
40
1
Order By: Relevance
“…This association suggested a regulatory role of hormones on appetite regulation and the onset of metabolic abnormalities. In contrast with our findings, other studies reported that exposure to high ambient temperatures and humidity under resting conditions caused poor appetite and reduced energy intake [51,52], which may be explained by some physiological factors such as reduced digestive enzyme activity and metabolic rate decrease [53].…”
Section: Discussioncontrasting
confidence: 99%
“…This association suggested a regulatory role of hormones on appetite regulation and the onset of metabolic abnormalities. In contrast with our findings, other studies reported that exposure to high ambient temperatures and humidity under resting conditions caused poor appetite and reduced energy intake [51,52], which may be explained by some physiological factors such as reduced digestive enzyme activity and metabolic rate decrease [53].…”
Section: Discussioncontrasting
confidence: 99%
“…Of note, dysfunctions in the serotonergic and dopaminergic systems have been also shown to play a role in the pathophysiological mechanisms underlying emotion dysregulation, which, in turn, is strongly linked to mood recurrences, impulsive behaviors, and substance abuse, ultimately leading to an increased risk of suicide in BD patients (53)(54)(55). Similarly, meteorological factors, including low barometric pressure, high temperatures and precipitations, have been associated with decreased sleep quality and abnormal circadian patterns (56,57), which, in turn, may represent a potential marker of SA in BD (58).…”
Section: Discussionmentioning
confidence: 99%
“…The present study also showed that nonoptimal temperature might inhibit the digestive enzyme activities. It would probably be the reason why temperature can affect the entomic appetite (Chen, Wong, Chan, & Wong, 2019;Zheng, Li, & Wang, 2019). In addition, simultaneous acute stressors may act in combination to alter normal immune function, and lead an additive or even synergistic effect (Ortuño, Esteban, & Meseguer, 2002).…”
Section: Discussionmentioning
confidence: 99%